Novel Implications of Exosomes in Diagnosis and Treatment of Cancer and Infectious Diseases - Wang, Jin (IntechOpen, 2017)
The aim of this book is to provide an overview of the importance of exosomes in the biomedical field, which involves in novel implications of exosomes in diagnosis and treatment of cancer and infectious diseases. The book would definitely be an ideal source of scientific information of exosomes to researchers and scientists involved in biomedicine, biology, and other areas involving cancer and infectious diseases.